Fiscal Multipliers - Spilimbergo, Antonio (IMF Staff Position Notes; Staff Position Note, 2009)
This paper provides background information for policymakers on fiscal multipliers, including quantitative estimates. The fiscal multiplier is the ratio of a change in output to an exogenous change in the fiscal deficit with respect to their respective baselines. The size of the multiplier is larger if: leakages are few; the monetary conditions are accommodative; and the country's fiscal position after the stimulus is sustainable. Fiscal expansions can be contractionary if they decrease consumers' and investors' confidence, especially if the fiscal expansion raises, or reinforces, fiscal sustainability concerns. Fiscal multipliers have been calculated for some countries but should be carefully re-examined considering the current events. The degree of financial market development has an ambiguous effect on multipliers, depending on how the degree of financial development affects liquidity constraints, and the government's ability to finance the fiscal deficit. The past research on multiplier estimates can provide guidance in developing multiplier estimates, but judgment, based on current conditions, is important.